Mission Possible: Creating a Spectacle with a Repetition of the Same Formula - Syamsi, Vera (ULTIMART Jurnal Komunikasi Visual, 2024)
A motion picture is one of the most popular spectacles people enjoy for various reasons, among others for entertainment. A film titled "Mission: Impossible” is one of the all-time most watched movies globally, since the first series was created in 1996. In the year 2023 it has come to the 7th series, and what has been released was only the first part, leaving its fans anxiously waiting for the end of the story. Many people would say there is nothing new in each of the series; the script writer applies the same ‘formula” to attract audience, however the series never fail to generate a lot of revenue, with the last rendition already be very popular and recorded as one of the box-office only within the first two days of its showing. In the era where spectacles are the pinnacle of day-to-day life for almost everyone, this research is going to investigate audience reception of the film "Mission: Impossible -Dead Reckoning Part One” in terms of the components of a spectacle, applying the concept of The Society of Spectacle by Debord (1967) which stated that a spectacle is built by utilizing "The Star, the Agent of Spectacle, False Choice / Pseudo needs and Détournement. The research focuses on the détournement by analyzing audience comments posted on a social media platform, investigating the reasons they love and hate the film, and the result will reveal how (un)successful the detournements are applied. Keywords: mission; impossible; spectacles; the society of spectacles; détournement; reception studies